2003
DOI: 10.1136/bjo.87.11.1409
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of cGMP in vitreous and subretinal fluid from eyes with retinal detachment

Abstract: Background: Cyclic guanosine monophosphate (cGMP) is produced in different retinal cells, including photoreceptor cells, wherein cGMP mediates photo-transduction. CGMP is degraded by phosphodiesterases (PDE). The aim was to investigate whether retinal detachment alters intraocular cGMP levels in human eyes. Methods: cGMP and PDE were determined in vitreous fluid from 50 eyes with a retinal detachment (group I) and in 20 control samples (group II) of vitreous fluid from eyes without retinal detachment. Group II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…42,43 Given the fact that cGMP is an important retinal player in general, and also in RP at least when PDE6A and PDE6B mutations are concerned, clinical measurements of cGMP levels in ocular tissue or in body fluids in various retinal states are few. In the context of retinal detachment, La Heij et al 44 have shown reduced cGMP levels in vitreous as well as subretinal fluid in patients with detached retinas, compared to control samples, and similar results have been obtained in experimental retinal detachments in pigs. 45 The reduced cGMP levels may have been due to lowered production of cGMP in the affected retinal cells.…”
Section: Purposesupporting
confidence: 63%
See 1 more Smart Citation
“…42,43 Given the fact that cGMP is an important retinal player in general, and also in RP at least when PDE6A and PDE6B mutations are concerned, clinical measurements of cGMP levels in ocular tissue or in body fluids in various retinal states are few. In the context of retinal detachment, La Heij et al 44 have shown reduced cGMP levels in vitreous as well as subretinal fluid in patients with detached retinas, compared to control samples, and similar results have been obtained in experimental retinal detachments in pigs. 45 The reduced cGMP levels may have been due to lowered production of cGMP in the affected retinal cells.…”
Section: Purposesupporting
confidence: 63%
“…45 The reduced cGMP levels may have been due to lowered production of cGMP in the affected retinal cells. 44,45 Interestingly, with respect to RP, a study by Martinez-Fernandez de la Camara and colleagues 15 reports elevated cGMP blood levels in RP patients. However, the authors do not discuss this in relation with high photoreceptor cGMP, but rather use the blood cGMP as an index of the activity of the NO/cGMP pathway and of oxidative stress as such.…”
Section: Purposementioning
confidence: 99%
“…When expressed in picomoles per milligram protein, our intracellular cGMP levels are comparable with cGMP levels found earlier in the rat retina [25] . In our previous study, the mean cGMP level in subretinal fluid from eyes with a retinal detachment was 2.4 n M [17] . In the current study, the extracellular cGMP concentration measured in the culturing media after 40 min of culturing, with or without IBMX, was maximally 0.16 n M .…”
Section: Discussionmentioning
confidence: 99%
“…However, less is known about cGMP synthesis and metabolism in RPE cells and the activation of both the soluble and the particulate guanylyl cyclases. Recently we found that retinal detachment was associated with a decrease in the cGMP concentration in the subretinal fluid as compared to controls [17] . The source of cGMP in subretinal fluid is unknown, as is the reason for the decrease in cGMP concentration after retinal detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing may progress following RRD, and the components of SRF may vary with time. van Setten et al 28 has reported that the concentrations of connective tissue growth factor in SRF changed over time, and La Heij et al 48 has stated that subretinal cGMP levels were moderately correlated with the duration of the retinal detachment. BakunowiczLazarczyk et al 30 noted that the concentration of IL-6 in SRF was significantly higher 5-8 weeks following RRD.…”
Section: Resultsmentioning
confidence: 99%